Channel transmission strategy for mmWave hybrid UAV communications with blockage. Issue 2 (1st January 2018) - Zhao, Jianwei; Jia, Weimin
Abstract : The blockage is a tough hurdle for millimetre‐wave (mmWave) unmanned aerial vehicle (UAV) communications. In this Letter, the authors propose an angle domain channel transmission scheme for mmWave hybrid UAV communication with blockage. Firstly, they investigate the angle domain channel transmission of mmWave UAV communication systems with massive array antennas. Then, they solve the blockage problem through the multi‐UAV coordination. Specially, they provide a practical user scheduling algorithm to maximize the achievable sum rates. Finally, simulation results are provided to show the effectiveness of the proposed method.